Synthesis of ZnO-TiO2 Nanoparticles by Sol-Gel Process and its Application for Solar Cell Semiconductor - Saridewi, Nanda; Riyanti, Aditya; Aziz, Isalmi; Niski Kumila, Biaunik; Lian Risa Adinda, Ade (Syarif Hidayatullah State Islamic University, 2023)
ZnO-TiO2 semiconductor can be used in Dye-Sensitized Solar Cell (DSSC) devices as an alternative to renewable energy. This semiconductor can be synthesized by sol-gel method. The objective of this study is synthesizing the TiO2-doped ZnO nanoparticle semiconductors for DSSC devices with mangosteen peel extract dye. Avocado seeds were extracted with water, as a capping agent in the synthesis of ZnO-TiO2 (TiO2 ratio of 0,3,5,7 and 10% to ZnO). XRD results show the success of ZnO-TiO2 doping, due to the 2θ shift and changes in the crystal lattice. The average crystal size obtained was 33.7972 nm. The SEM results showed that the particle size of ZnO ranged from 45-100 nm. The UV-Vis dye measurements of mangosteen peel extract showed an absorption peak at 296-483 nm wavelength, with a corresponding band gap energy value of 3.04 eV. The UV-Vis DRS ZnO-TiO2 measurements have an average band gap energy of 3.1425 eV and ZnOof 3.1915 eV. The highest DSSC efficiency value is 2.15 x 10-2% at 7% ZnO-TiO2 semiconductor.